La Sobreprotección infantil y el desarrollo conductual en niños de preparatoria de la Unidad Educativa Fiscomisional “Santa Mariana de Jesús” período 2024 - Romero Ortega, Gina Maribel (2024)
Child overprotection is an important aspect that can negatively influence the quality of life and educational performance of the student. This study aimed to analyze child overprotection in the behavioral development of high school children of the Unidad Educativa Fiscomisional "Santa Mariana de Jesús". The methodological design comprises a qualitative approach, descriptive type, non-experimental, transversal design, and scientific and deductive methods. The interview guide and observation form were applied to high school students "A" and a teacher. Through triangulation, it was possible to identify the effects of child overprotection on behavioral development; several students showed dependence on their parents to perform daily tasks such as dressing or eating alone. It is concluded that overprotection is an influential factor in behavioral development, as they may show a lack of interest in schoolwork and require constant supervision to complete it. Keywords: child overprotection, behavioral development, students, parents.